Penerjemahan Mushaf Al-Qur’an Ke Dalam Bahasa Isyarat Untuk Tunarungu - Ahmad Jamil; Nidhiom, Khoirun (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2024)
In the practice of reading the Qur'an there are many methods or procedures to be able to read the Qur'an properly and correctly. Deafness has an unfavorable impact on sufferers, this impact is like experiencing anxiety because they face a variety of communication environments. In general, their emotions are less stable due to their poor language, so they have low self-esteem and are easily offended. This is what causes them difficulties in learning the recitation of the Qur'an. The purpose of this study was to determine the inhibiting and supporting factors for the ability to read the Qur'an in deaf children. Hearing loss causes difficulties in learning and reading the Qur'an properly. The researcher found that this research was interesting to be used as research material in special schools for special students, including students experiencing deaf problems in reading the Qur'an. Hearing loss causes difficulty in learn and read the Al-Qur’an properly. The sense of hearing is very important to help someone speak. This is because hearing and speech are closely related. Therefore, if any defects occur in parts of the auditory process, it will affect the ability to hear and speak spoken language.